Applicability of American Joint Committee on Cancer and College of American Pathologists Regression Grading System in Rectal Cancer. Issue 8 (August 2017) - Jäger, Tarkan; Neureiter, Daniel; Urbas, Romana; Klieser, Eckhard; Hitzl, Wolfgang; Emmanuel, Klaus; Dinnewitzer, Adam
Abstract : BACKGROUND: Different tumor grading systems have been proposed to predict the association between tumor response and clinical outcome after preoperative chemoradiotherapy in patients with rectal cancer. The American Joint Committee on Cancer and College of American Pathologists regression grading system was recommended as the standard tumor regression grading system for rectal adenocarcinoma. OBJECTIVE: This study evaluated the clinical applicability of the American Joint Committee on Cancer and College of American Pathologists regression grading system in neoadjuvant-treated patients with rectal cancer. DESIGN: This is a retrospective cohort study based on clinical data from a prospectively maintained colorectal cancer database. SETTINGS: This study was performed at a single tertiary referral center. PATIENTS: A total of 144 patients with primary locally advanced mid-to-low rectal adenocarcinoma who underwent preoperative long-course chemoradiotherapy and total mesorectal excision between 2003 and 2012 were included. MAIN OUTCOMES MEASURES: The primary outcome measures were the 5-year overall survival rate, the relapse-free survival rate, the cancer-specific survival rate, and cumulative recurrence rates. RESULTS: Of the 144 patients, 16 (11%) were diagnosed as American Joint Committee on Cancer and College of American Pathologists regression grade 0, 43 patients (30%) as grade 1, 61 patients (42%) as grade 2, and 25 patients (17%) as grade 3. After a median follow-up time of 83 months (range, 3 to 147 mo), 5-year survival estimates for grades 0, 1, 2, and 3, were 93%, 77%, 81%, and 54% for overall survival ( p = 0.006); 93%, 82%, 75%, and 55% for relapse-free survival ( p = 0.03); and 100%, 86%, 89%, and 63% for cancer-specific survival ( p = 0.006). The multivariate Cox regression analyses confirmed the American Joint Committee on Cancer and College of American Pathologists regression grading system as a prognostic factor for overall ( p = 0.04), relapse-free ( p = 0.02), and cancer-specific survival ( p = 0.04). LIMITATIONS: This was a retrospective study. CONCLUSIONS: Our study findings confirm the clinical relevance and applicability of the American Joint Committee on Cancer and College of American Pathologists regression grade system as a predictive factor for patients with rectal cancer.See Video Abstract athttp://links.lww.com/DCR/A320 .